Impacts of forestry drainage on surface peat stoichiometry and physical properties in boreal peatlands in Finland - Turunen, Jukka; Anttila, Jani; Laine, Anna M.; Ovaskainen, Juha; Laatikainen, Matti; Alm, Jukka; Larmola, Tuula (Springer Nature, 2024)
Management of drained peatlands may pose a risk or a solution on the way towards climate change mitigation, which creates a need to evaluate the current state of forestry-drained peatlands, the magnitude of degradation processes and indicators for carbon (C) loss. Using a large dataset (778 profiles, 891 peat samples, collected between 1977 and 2017) from peatlands having different fertility classes across Finland, we investigate whether the surface peat profiles of undrained and forestry-drained peatlands differ in C:N, von Post and dry bulk density. The utility of element ratios (C:N:H stoichiometry) as site indicators for degradation were further analyzed from a subsample of 16 undrained and 30 drained peat profiles. This subsample of drained sites had carbon dioxide (CO2) and methane (CH4) fluxes measured allowing us to link peat element ratios to annual C gas effluxes. Element ratios H:C, O:C and C:N and degree of unsaturation (combining C, N, H changes) were found widely valid: they captured both differences in the botanical origin of peat as well as its potential decomposition pathway (C lost via a combination of dissolved organic C and C gas loss and/or the gaseous loss predominantly as CO2). Of the stoichiometric indexes, peat H:C ratio seemed to be the best proxy for degradation following drainage, it indicated not only long-term degradation but also explained 48% of the variation in annual CO2 emission. The O:C ratio positively correlated with annual CH4 flux, presumably because high O:C in peat reflected the availability of easily degradable substrate for methanogenesis. The differences in C:N ratio indicated notable decomposition processes for Sphagnum-dominated peatlands but not in Carex-dominated peatlands. Degree of unsaturation showed potential for an integrative proxy for drainage-induced lowering water table and post-drainage changes in peat substrate quality.
The data sets of the Geological Survey of Finland and Natural Resources Institute Finland analyzed in this study deposited in Zenodo: https://doi.org/10.5281/zenodo.8434148, https://doi.org/10.5281/zenodo.10068486 & https://doi.org/10.5281/zenodo.10068778.
Keywords: Peat stoichiometry; Forestry-drained peatlands; Element ratios; C:N; H:C; O:C